Anredera cordifolia (Ten.) Steenis (Basellaceae) : potencial antimicrobiano e fungos endofíticos - Alves, Felipe Lazaro (2023)
The medicinal plant known in Brazil as “bertalha”, Anredera cordifolia (Ten.) Steenis, is popularly used in the treatment of infections and wounds, and some studies report antimicrobial action of crude extracts. The plant has several secondary metabolites of pharmacological interest, especially saponins, which have already been detected in all parts of the plant. Endophytic fungi are microorganisms found inside plants during all or at least part of their life cycle without causing damage to the host. They stand out for their ability to produce secondary metabolites similar to those produced by plants, as well as for their bioactive properties that are possibly derived from metabolic interactions. This dissertation is organized in a bibliographic review, which brings a brief description of the A. cordifolia plant, secondary metabolites, mainly saponins, medicinal plants and endophytic fungi. In a second moment, the scientific production stands out, which aimed to isolate and identify the endophytic fungi present in the leaves of the plant and to test the leaf extracts of A. cordifolia in the control of human pathogens. With regard to endophytic fungi, the following genera were isolated and identified: Aspergillus, Fusarium, Scedosporium and Alternaria. Regarding the antimicrobial activity, the extracts did not inhibit the growth of microorganisms under the tested conditions.